Spatial patterns and drivers of fish and benthic reef communities at São Tomé Island, Tropical Eastern Atlantic - Hugulay A. Maia; Renato A. Morais; Juan Pablo Quimbayo; Murilo S. Dias; Claudio L. S. Sampaio; Paulo A. Horta; Carlos Eduardo L. Ferreira; Sergio R. Floeter (Marine Ecology, 2018)
Marine communities vary across spatial scales due to changes in habitat structure, wave exposure, depth and anthropogenic activities. Here, we quantitatively characterized, for the first time, the reef fish assemblages and benthic communities in six sites around São Tomé Island, in the Tropical Eastern Atlantic region. We performed 139 underwater visual census and 112 photo‐quadrats across six sites around the island to explore the relative importance of exposure, depth and topographic complexity as drivers of fish and benthic reef communities. Planktivores were the most important trophic group, in terms of both fish abundance and biomass. Small fishes (0–7 cm) dominated the abundance, whereas biomass was mainly concentrated in 8–15 and 16–30 cm body size classes. About 30% of the total benthic cover was composed of turf algae and circa of 28% of calcareous coralline algae, whereas corals were comparably less abundant (only 8%). Among these, Montastraea cavernosa was the most abundant coral (46% of the coral cover and 4% of total benthic cover). Wave exposure was the most important driver of the reef fish assemblages and was also important for benthic communities. Also, fish species composition seemed to respond, although weakly, to benthic composition. Topographic complexity had little effect on the indicators of fish assemblages but seemed to drive some changes in benthic cover. Overall, our results evidence the dominance of small planktivorous reef fish assemblages and of turf algal communities in São Tomé. Taken together, they support the idea of benthic communities shaped by wave action, with minor importance of corals, and of important energetic contribution from planktonic material. We also suggest that the relatively low biomass of medium and large fish species reflects the long‐term fishing pressure in São Tomé Island.